When the Bear Comes to Town: How the City Could Create Nature - Roggema, Rob; Rodriguez, Diego; Tillie, Nico (Urban Planning and Construction, 2024)
The relationship between humans and nature is in permanent change. Where the city and nature used to be seen as enemies that needed to be kept away from each other, the current paradigm looks at a more symbiotic relationship. In this, man is seen as part of nature, and the city is seen as a determining factor in providing conditions for a rich urban ecology. In this study, urban conditions are seen as the starting point for urban design, enabling biodiversity to thrive. The aim of the research is to distill design strategies that enhance nature in an urban context. These strategies are derived from existing theories, the typical relationship between the city and nature, and the understanding of the natural landscape, and are applied in the heated, dry, and rocky conditions in the metropolitan region of Monterrey, Mexico. The main finding is that the city contains ecologies with their own characteristics, often distinct from rural or natural ecologies. These specific conditions can be amplified using adequate design strategies, which may lead to a greater biodiversity. For improving urban biodiversity, the perspective on the city shall be transformed from seeing it as an enemy of nature towards a symbiotic relationship between the two. At the same time, this perspective requires additional research into two main aspects: the way the city is able to create its own climatic conditions, and how landscape-based design can enhance the urban conditions in a way nature occupies these novel ecological niches.